Research on the selection of components for the creation of a medicine for the treatment of seboreic dermatitis of the scalp - Konovalenko , Ilona; Cherkasova , Albina (Annals of Mechnikov's Institute, 2023)
Introduction. Seborrheic dermatitis is a chronic recurrent skin disease associated with increased secretion of skin sebum, a change in its qualitative composition, and is characterized by localization in areas of accumulation of sebaceous glands - on the scalp, face, upper body, folds. Scaling of the scalp accompanied by itching creates not only medical, but also social and psychological problems for patients, especially in field military operations, where access to medical supplies and conditions for personal hygiene may be limited, and stress is the main pathogenetic link for exacerbation of seborrheic dermatitis. Therefore, this causes the interest of considering the main aspects of this dermatosis, as well as ensuring high-quality and safe treatment of seborrheic dermatitis in field military conditions and the development of new drugs. Purpose of the study. The purpose of our research was to conduct an analysis of drugs on the pharmaceutical market of Ukraine and, based on the results, to develop a composition and develop an algorithm for creating a new drug in the form of a mask-balm for the treatment of seborrheic dermatitis of the scalp. Materials and methods. In order to determine the relevance of the creation of new drugs of extemporaneous production, the next stage of research was to analyze literature data. Research methods: information-research, physico-chemical, rheological, organoleptic. Results & Discussion. As a result of the literature analysis of the assortment of dermatological preparations, it was determined that the assortment of medicinal and cosmeceutical preparations manufactured in a pharmacy does not satisfy the needs of the consumer who suffers from manifestations of seborrheic dermatitis of the hairy part of the scalp in full. The selection of the concentration of active pharmaceutical ingredients was justified by literature data on the relativity of the therapeutic effect to its percentage of introduction into the soft dosage form for application purpose. All components are physically and chemically compatible when mixed with each other and exhibit the declared pharmacological effect. It was found that samples with structural viscosity values in the range of (2000 – 10000) mPa·s at 20 rpm have optimal structural and mechanical indicators. The study of the sensory properties of the balm-mask for the treatment of seborrheic dermatitis of the scalp allowed us to choose sample No. 3, which met all the requirements of the regulatory documentation for quality indicators, did not change its properties during storage for 1 month, and satisfied the users' requirements for sensory properties. When analyzing the obtained results, we came to the conclusion that according to the main criteria, the balsam-mask sample obtained meets the requirements of regulatory documentation. Conclusions. 1. The conducted informational and analytical analysis made it possible to establish that, at present, combined drugs for the treatment of seborrheic dermatitis of the scalp of extemporaneous production are presented in insufficient quantities. 2. The development of new multifunctional cosmeceutical preparations for application in the form of a balm-cream containing active substances with complex therapeutic activity (anti-inflammatory, wound healing, antibacterial and mild exfoliating effect) is an urgent task of modern pharmacy. 3. The concentration of zinc-pyrithione, azelaic, glycolic and lactic acids active substances, which would show the claimed effect, was selected. 4. A study was conducted on the selection of auxiliary substances and their concentration. It was determined that the optimal emulsifier is Emulfarma 1000. Rheological and organoleptic (sensory) studies of the obtained experimental samples of balm-cream were carried out. Keywords: medicine, seboreic dermatitis, scalp